Find the vertex of the parabola with an equation y=-(-x-2)(x-4)
1 answer:
Answer:
(3,1)
Step-by-step explanation:
We can have the equation of the parabola re-written
the general form is;
y = a(x-h)^2 + k
where (-h,k) is the vertex
so we have
y = -1(x^2 -6x + 8)
y = -1(x^2 -6x + 9 - 1)
y = -1(x-3)^2 - 1)
y = -1(x-3)^2 + 1
So we have the vertex of the parabola as;
(3,1)
You might be interested in
I’m ok lots of school work
She should multiply the quotient by 48.
Answer:
-0.2 > -0.6
Step-by-step explanation:
The closer to zero the greater it is
The answer is 0.6666666666 but to simplify it you can put 0.6
Answer:
5/11
Step-by-step explanation: